Infl uence of Pursed-Lips Breathing to Improve Quality of Life in Chronic Obstructive Pulmonary Disease Patients - Meldy Muzada Elfa; Eko Budiono; Heni Retnowulan (Faculty of Medicine Universitas Gadjah Mada, 2019)
Background. Worsening of Chronic Obstructive Pulmonary Disease (COPD) may decrease the quality of life of patients. Rehabilitation of patients with COPD may increase exercise tolerance and improve quality of life. Pursed-Lips Breathing (PLB) activates abdominal muscles during expiration for improving gas exchange and oxygen saturation in the arteries, increasing the tidal volume and reduce shortness of breath, anxiety, and tension thus improving the quality of life. St George's Respiratory Questionnaire (SGRQ) was a tool to measure the quality of life of patients with COPD, which has been validated. Patients with improved quality of life were characterized by a decrease in the SGRQ score after PLB training.Aims. Analyze the effect of improved quality of life in patients with stable COPD using PLB + standard therapy compared to standard therapy only.Methods. This research used an open-label Randomized Controlled Trial (RCT) design and conducted in patients with COPD stages 2 and 3. It was performed in Rumah Sakit Khusus Paru (RSKP) Respira Bantul, Yogyakarta. The study group was composed of 47 subjects, who continued the previous standard therapyand performed PLB 8 minutes once a day for 28 days. The placebo group (44 samples) continued the previous standard therapy alone. Measuring the quality of life using the SGRQ performed in both groupsbefore and after the experiment. Statistical analysis included independent t-test and Mann Whitney U-test.Results. Th ere were improvements in the quality of life that clinically characterized by a decrease in SGRQ total score of 12.19 points out of 100 points total in the PLB group. Th ere was a very significant difference in the decline in total SGRQ score between the study group and placebo groups (p <0.001).Conclusion. Pursed-Lips Breathing (PLB) improves the quality of life of patients with stable COPD was characterized by a decrease in SGRQ of 12.19 points out of 100 points total.Keywords. COPD (Chronic Obstructive Pulmonary Disease), PLB (Pursed-Lips Breathing), SGRQ (St George’s Respiratory Questionnaire), quality of life